Association of Monocyte Count on Admission with the Angiographic Thrombus Burden in Patients with ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Wang,Zuoyan (2018)
Abstract Background: The intracoronary high-thrombus burden during the primary percutaneous coronary intervention in patients with ST-elevation myocardial infarction (STEMI) can lead to poor outcomes. Monocytes have been described to play an important role in thrombotic disorders. Objectives: This study aimed to investigate the relationship between admission monocyte count and angiographic intracoronary thrombus burden in patients receiving primary percutaneous coronary intervention (PPCI). Methods: A total of 273 patients with acute STEMI who underwent PPCI were enrolled. The patients were divided into two groups according to the thrombolysis in myocardial infarction (TIMI) thrombus grade: low-thrombus burden group with a grade of 0-2 and high-thrombus burden group with a grade of 3-4. The monocyte count and other laboratory parameters were measured on admission before PPCI. P-value < 0.05 was considered significant. Results: There were 95 patients (34.8%) in the high-thrombus burden group, and 178 patients (65.2%) in the low-thrombus burden group. Patients with high-thrombus burden had significantly higher admission monocyte count (0.61 ± 0.29×109/L vs. 0.53 ± 0.24×109/L, p = 0.021). In multivariate analysis, monocyte count was the independent predictor of angiographic high-thrombus burden (odds ratio 3.107, 95% confidence interval [CI] 1.199-7.052, p = 0.020). For the prediction of angiographic high-thrombus burden, admission monocyte count at a cut-off value of 0.48×109/L yielded 0.59 ROC-AUC (71.9% sensitivity, 46.9% specificity). Conclusions: Monocyte count on admission was an independent clinical predictor of high-thrombus burden in patients with STEMI undergoing PPCI. Our findings suggest that admission monocyte count may be available for early risk stratification of high-thrombus burden in acute STEMI patients and might allow the optimization of antithrombotic therapy to improve the outcomes of PPCI.